STRATEGI MANAJEMEN REDAKSI MEDIA ONLINE WASPADA.CO.ID DALAM MENGHADAPI PERSAINGAN MEDIA DIGITAL - Sayyid Musafa Alwan; Erwan Efendi (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
This study aims to analyze the editorial management strategies implemented by Waspada.co.id in facing the increasingly competitive digital media environment. The rapid development of communication technology and the growing public demand for real-time information have encouraged online media organizations to continuously innovate in newsroom management and news presentation. This research employed a qualitative approach with a descriptive method to gain an in-depth understanding of editorial strategies, workflows, and management dynamics within Waspada.co.id. Data were collected through in-depth interviews, observations, and documentation of editorial activities. The findings reveal that the editorial management strategies applied by Waspada.co.id are adaptive, innovative, and sustainable while consistently adhering to journalistic ethics. The utilization of social media as a platform for information distribution and media branding, the implementation of multimedia concepts in news presentation, and content adjustments based on audience characteristics constitute essential components of the company’s competitive strategy. Furthermore, strengthening human resource quality through journalist training, structured editorial coordination, and the development of extensive information networks significantly support the effectiveness of newsroom management. The study concludes that the integration of digital innovation, journalistic quality, and human resource management plays a crucial role in maintaining the sustainability and competitiveness of online media in the digital era. Keywords: Editorial Management, Online Media, Media Strategy, Digital Journalism, Waspada.co.id